Risk factors of concurrent malnutrition among children in Ethiopia: a bivariate spatial modeling approach. Issue 1 (31st December 2022) - Egbon, Osafu Augustine; Belachew, Asrat Mekonnen; Bogoni, Mariella Ananias
Abstract : Malnutrition among children remains a challenge to public health in Africa, and it is responsible for the increased infant mortality rate in Ethiopia. This study aims to identify the joint determinant factors of malnutrition among under-age five children in Ethiopia and quantify the regional prevalence across the country. A Bayesian hierarchical linear mixed model, with a bivariate conditional autoregressive model, was adopted to account for the joint spatial prevalence pattern of malnutrition among under-age five children in Ethiopia. The data were provided by the Demography and Health Surveys program. The study revealed that gender, wealth index, mothers' education, toilet system, fever, birth order, birth interval, contraceptive use, and diarrhea, are significant risk factors of child malnutrition. The three malnutrition indicators are most prevalent in the Afar region, while stunting and underweight are most prevalent in Amhara, Beneshangul Gumuz, and Tigray, and the wasting and underweight are most prevalent in the Gambela and Somali. Findings revealed that a stunted child is more likely to be underweight than being wasted, and a wasted child is more likely to be underweight than being stunted. The findings also revealed significant changes in the prevalence of malnutrition for different mothers and children age groups. For cost-effective malnutrition intervention, programs for parents, such as awareness creation about the modern types of contraceptives, appropriate birth spacing, the benefits of antenatal and postnatal care, for example, are a propitious method to mitigate malnutrition in high prevalent regions than direct intervention to the children. Abbreviations : BICAR, Bivariate Conditional Autoregressive; DHS, Demographic and Health Survey; EDHS, Ethiopia Demographic and Health Survey; EA, Enumeration Area; GMRF, Gaussian Markov Random Field; HAZ, Height for Age Z-sscore; INLA, Integrated Nexted Laplace Approximation; MCAR, Multivariate Conditional Autoregressive; MCMC, Markov Chain Monte Carlo; SNNPR, Southern Nations, Nationalities, and People's Region; WAZ, Weight for Age Z-score; WHZ, Weight for Height Z-score; WHO, World Health Organization